Preparation and Hydrogelling Performances of a New Drilling Fluid Filtrate Reducer from Plant Press Slag - Wenjun Long; Xialei Zhu; Fengshan Zhou; Zhen Yan; Amutenya Evelina; Jinliang Liu; Zhongjin Wei; Liang Ma (Gels, 2022)
Plant press slag (PPS) containing abundant cellulose and starch is a byproduct in the deep processing of fruits, cereals, and tuberous crops products. PPS can be modified by using caustic soda and chloroacetic acid to obtain an inexpensive and environmentally friendly filtrate reducer of drilling fluids. The optimum mass ratio of mNaOH:mMCA:mPPS is 1:1:2, the optimum etherification temperature is 75 °C, and the obtained product is a natural mixture of carboxymethyl cellulose and carboxymethyl starch (CMCS). PPS and CMCS are characterized by using X-ray diffraction, scanning electron microscopy, Fourier transform infrared spectroscopy, thermogravimetric, X-ray photoelectron spectroscopy, and elemental analysis. The filtration loss performance of CMCS is stable before and after hot-rolling aging at 120 °C in 4.00% NaCl and saturated NaCl brine base slurry. The minimum filtration loss value of CMCS is 5.28 mL/30 min at the dosage of 1.50%. Compared with the commercial filtrate reducers with a single component, i.e., carboxymethyl starch (CMS) and low viscosity sodium carboxymethyl cellulose (LV-CMC), CMCS have a better tolerance to high temperature of 120 °C and high concentration of NaCl. The filtration loss performance of low-cost CMCS can reach the standards of LV-CMC and CMS of the specification of water-based drilling fluid materials in petroleum industry.